THE INFLUENCE OF EDUCATION BUDGET ON INCOME INEQUALITY BETWEEN REGIONS IN BANTEN PROVINCE - Rahayu Purwaningsih, Murni
The regional development paradigm still prioritizes economic growth, whereas income distribution as a secondary issue. One of the functions of the government is to allocate the budget for public to reduce inequality, by using resources efficiently. The education budget has been set at a mandatory 20% of the APBN and APBD. However, education in Indonesia still faces problems, such as low quality of education and inequality in access to education. The quality of public education will affect the quality of human resources, and the quality of human resources will affect the chances of getting a job and the income earned. The objectives of regional expansion are economic growth and reducing inequality. Banten Province is one of the expansion provinces, which has a problem of income inequality between regions, and since the division, inequality has tended to increase. The education budget in Banten Province has reached 20% of the APBD, the HDI score is ranked 8th nationally, and GRDP per capita has increased every year, but income inequality is still a complex problem to be faced. Previous research has mostly focused on the relationship between education and income inequality, but relatively few have studied the effect of fiscal policy on income inequality. Therefore, this study seeks to analyze the effect of the education budget on income inequality in Banten Province, and in the context of regional planning, whether there is a spatial influence in the linkage of the education budget to income inequality in Banten Province. This study uses the Williamson index and Theil entropy index to identify income inequality between regions of Banten Province. According to the study's findings, there is income inequality between districts/cities, and also within regions. Using panel data regression analysis with the fixed effect (FE) method to identify the pattern of the relationship between the education budget and inequality interregional income and using spatial error model (SEM) to analyze spatial patterns of income inequality between regions. The findings of the regression with the fixed effect show that the education budget has a negative and significant effect, while TPT and the number of poor people have a positive and significant effect on inter-regional income inequality in Banten Province. The education budget influences indirectly and has a direct impact on other variables first. Therefore, the influence of the education budget will have a significant impact on reducing income inequality between regions in the long term. The level of income inequality in a district/city affects in other adjacent district/city, with a TPT as a significant causal factor, while the education budget has no significant effect on income inequality between adjacent districts/cities. The findings of this study are expected to be taken when government policies regarding education budget allocations are made, as well as to reduce income inequality. In addition, it is also expected to broaden academic insight and understanding regarding the influence of fiscal on regional planning